Implementation of Problem-Based Learning Based on Culturally Responsive Teaching to Improve Students' Mathematical Literacy - Agustiningtyas, I'in Triana; Dristian, Umi; Ismail, Agung Deddiliawan (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
Mathematical literacy is essential for students to face the challenges of the 21st century. This ability encompasses mastery of mathematical concepts and procedures, reasoning skills, and the capacity to solve contextual problems. PBL is a learning model that solves real-world problems. However, its application in a culturally relevant context that aligns with students' experiences and backgrounds remains limited. This study examines the application of CRT-based PBL to improve students' mathematical literacy. The CRT approach emphasizes linking the learning environment with local culture, while PBL is a problem-based learning model. To increase student engagement in the learning process, the problem context used is the students' local culture. The research method used is CAR, with two learning cycles including planning, implementation, observation, and reflection. Data analysis of mathematical literacy test results used quantitative and qualitative descriptive analysis techniques. To measure changes in mathematical literacy, data collection was carried out through mathematical literacy tests and observations. Based on the results of data analysis, there was an increase in the average post-test score of students in each learning cycle. Therefore, it proves that the implementation of the CRT-based PBL model can improve mathematical literacy and student engagement in the learning process. Students could also relate mathematical concepts to cultural contexts familiar to them. Therefore, PBL combined with CRT can be an alternative solution to optimally enhance students' mathematical literacy by providing relevant and meaningful learning experiences.